Severe Hypoglycemia Accompanied with Thyroid Crisis - Yuki Nakatani; Tsuyoshi Monden; Minoru Sato; Nozomi Domeki; Mihoko Matsumura; Nobuyuki Banba; Takaaki Nakamoto (Case Reports in Endocrinology)
We report a 32-year-old Japanese women with severe hypoglycemia accompanied with thyroid crisis. She complained of dyspnea, general fatigue, and leg edema. She was diagnosed with hyperthyroidism with congestive heart failure and liver dysfunction. Soon after admission, sudden cardiopulmonary arrest occurred. She was then transferred to the intensive care unit. Her serum glucose level was 7 mg/dl. Intravenous glucose, hydrocortisone, diuretics, and continuous hemodiafiltration (CHDF) saved her. We considered that hypoglycemia occurred due to heart failure and liver dysfunction due to thyroid crisis.